Efficacy and Safety of Laparoscopic Appendectomy: A Comparative Study - Miylikulovich, Musurmonov Aminjon (American Journal of Bioscience and Clinical Integrity, 2024)
Laparoscopic appendectomy (LA) has gained prominence as a minimally invasive surgical technique for treating acute appendicitis due to its benefits, including reduced postoperative pain and faster recovery compared to open appendectomy (OA). Despite extensive studies on the efficacy of LA, gaps remain regarding long-term outcomes and the influence of patient demographics and surgeon experience on recovery. This study aims to compare the efficacy and safety of LA and OA by retrospectively analyzing clinical data from 200 patients who underwent appendectomy at [insert hospital] between 2010 and 2023. The analysis evaluated postoperative pain, hospital stay duration, complication rates, and patient satisfaction. The findings revealed significantly lower pain scores (3.1 vs. 5.6), shorter hospital stays (2.3 vs. 4.5 days), and reduced complication rates (4% vs. 12.5%) in the LA group compared to the OA group. Patient satisfaction was notably higher in the LA cohort (8.7 vs. 6.4). These results confirm the advantages of LA in improving patient outcomes and minimizing postoperative trauma. The study’s implications suggest a need for enhanced surgeon training in laparoscopic techniques and increased patient education. Further research is recommended to explore long-term outcomes, surgeon proficiency, and cost-effectiveness to optimize surgical protocols for appendicitis management.